Food Insecurity, Neighborhood Food Access, and Food Assistance in Philadelphia - Mayer, Victoria L. (J Urban Health, 2014)
An estimated 17.6 million American households were food insecure in 2012, meaning they were unable to obtain enough food for an active and healthy life. Programs to augment local access to healthy foods are increasingly widespread, with unclear effects on food security. At the same time, the US government has recently enacted major cuts to federal food assistance programs. In this study, we examined the association between food insecurity (skipping or reducing meal size because of budget), neighborhood food access (self-reported access to fruits and vegetables and quality of grocery stores), and receipt of food assistance using the 2008, 2010, and 2012 waves of the Southeastern Pennsylvania Household Health Survey. Of 11,599 respondents, 16.7 % reported food insecurity; 79.4 % of the food insecure found it easy or very easy to find fruits and vegetables, and 60.6 % reported excellent or good quality neighborhood grocery stores. In our regression models adjusting for individual- and neighborhood-level covariates, compared to those who reported very difficult access to fruits and vegetables, those who reported difficult, easy or very easy access were less likely to report food insecurity (OR 0.62: 95 % CI 0.43–0.90, 0.33: 95 % CI 0.23–0.47, and 0.28: 95 % CI 0.20–0.40). Compared to those who reported poor stores, those who reported fair, good, and excellent quality stores were also less likely to report food insecurity (OR 0.81: 95 % CI 0.60–1.08, 0.58: 95 % CI 0.43–0.78, and 0.43: 95 % CI 0.31–0.59). Compared to individuals not receiving food assistance, those receiving Supplemental Nutrition Assistance Program (SNAP) benefits were significantly more likely to be food insecure (OR 1.36: 95 % CI 1.11–1.67), while those receiving benefits from the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) (OR 1.17: 95 % CI 0.77–1.78) and those receiving both SNAP and WIC (OR 0.84: 95 % CI 0.61–1.17) did not have significantly different odds of food insecurity. In conclusion, better neighborhood food access is associated with lower risk of food insecurity. However, most food insecure individuals reported good access. Improving diet in communities with high rates of food insecurity likely requires not only improved access but also greater affordability.